Character Education of Students through the Mutiara Desa Program and Osing Cultural Immersion - Erma Hari Tri Astuti; Akhmad Affandi (INCARE, International Journal of Educational Resources, 2026)
Character education has become a crucial component in addressing the challenges of globalization and digitalization, which may weaken the moral values of younger generations. The Mutiara Desa program represents an experiential learning innovation that integrates contextual education with the introduction of Osing local culture. This study aims to analyze the implementation of the Mutiara Desa program in shaping students’ character and to examine its relevance to the principles of Islamic educational philosophy. This research employs a qualitative approach with a case study design conducted at SMPN 1 Banyuwangi. Data were collected through participatory observation, in-depth interviews with students, foster families, and accompanying teachers, as well as documentation, and analyzed using thematic analysis. The findings indicate that students’ engagement in social and cultural village activities significantly enhances empathy, social responsibility, independence, and appreciation of local culture. Furthermore, the program reflects key Islamic educational concepts such as ta’dib and tazkiyatun nafs through direct experiences that facilitate deep value internalization. This study contributes to the development of an integrative, contextual, and experience-based character education model relevant to formal education in Indonesia.